Penggunaan Metode Network Pada Pembangunan MBG di Medan Amplas - murdiah; Rani Padila Ningsih; Putri Khoirunnisa; Ahmad Albar Tanjung (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study seeks to evaluate how effective the Network Planning method is when using the Critical Path Method (CPM) and Program Evaluation and Review Technique (PERT) in scheduling the construction of the Free Nutritious Food Program (MBG) facility in Medan Amplas District. A descriptive quantitative research method was used, involving data collection through field observations and interviews with those managing the project. The data were processed using QM for Windows software to identify the critical path and estimate the project's completion time. The findings show that the ideal completion time for the MBG project is 72 days, which is faster than the actual time taken, which was 90 days. The critical path for the project was found to be A–C–D–E–F–G–H–I–N–O–P–Q–T. The results highlight that using CPM and PERT enhances time efficiency and improves the ability to manage the project effectively. As a result, Network Planning acts as a valuable tool for project managers to help ensure the successful execution of government infrastructure projects.